(untitled) (PERcursos Linguísticos, 2024)
ABSTRACT: The linguistic-sensory experience of deafblindness has been described as a disability represented by a double sensory impairment. This article aims to discuss the language potential of the experience of deafblindness. To this end, based on the perspective of indisciplinary applied linguistics and disability studies, it explores elements identified in a bibliographical research that selected national academic and scientific productions on forms of communication used by people with deafblindness. Considering the situation of linguistic systems that permeate the existence of deafblind people, as well as the necessary correlation between some of them to establish understanding and expression, it is argued that deafblindness constitutes a translingual experience insofar as its linguistic-sensory possibilities offer broad conditions for the exercise of language in its most varied forms. KEYWORDS: Deafblindness. Disability. Translanguaging.